2021
DOI: 10.1111/cas.15126
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fusobacterium nucleatum and antitumor immunity in colorectal cancer liver metastasis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…In this study, we have elucidated that F. nucleatum administration promotes CRLM and is correlated with the activation of hepatic immune microenvironment. Interestingly, a recent study has innovatively demonstrated that F. nucleatum can be detected in liver metastases and the F. nucleatumpositive CRLM are associated with the reduced density of T cells [32]. Consistent with these findings, using in vivo murine models of CRC, we have shown that F. nucleatum reshapes the immune microenvironment in metastatic livers.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we have elucidated that F. nucleatum administration promotes CRLM and is correlated with the activation of hepatic immune microenvironment. Interestingly, a recent study has innovatively demonstrated that F. nucleatum can be detected in liver metastases and the F. nucleatumpositive CRLM are associated with the reduced density of T cells [32]. Consistent with these findings, using in vivo murine models of CRC, we have shown that F. nucleatum reshapes the immune microenvironment in metastatic livers.…”
Section: Discussionsupporting
confidence: 88%
“…F. nucleatum induced a dramatic decrease in m 6 A modification in CRC cells and patient-derived xenograft tissues through downregulation of the m 6 A methyltransferase METTL3, resulting in CRC aggressiveness (95). A study quantified F. nucleatum DNA in 181 colorectal cancer liver metastasis (CRLM) specimens and found that F. nucleatumpositive CRLM showed a significantly lower density of CD8 + T cells and a higher density of MDSCs compared to F. nucleatumnegative CRLM, and the difference was statistically significant, but the relationship between F. nucleatum and density of tumorassociated macrophages (TAMs) was not statistically significant (96). F. nucleatum may be a biomarker of CRC (97).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Meanwhile, cytokines (IL-10, IL-17) secreted by activated M2 macrophage, in turn, promote CRC cells invasion and metastasis by activating NF-κB pathway ( 79 ). Fusobacterium nucleatum can boost liver metastasis by modulating liver microenvironment featured with accumulation of MDSCs, and reduction of NK and Th17 cells ( 80 , 81 ). Peptostreptococcus anaerobius was also reported to induce chronic inflammation and modulate tumor microenvironment by recruiting MDSCs, TANs and TAMs ( 82 ).…”
Section: Gut Dysbiosis Facilitates Immune Escape In Crcmentioning
confidence: 99%